2022
DOI: 10.1503/cmaj.212147
|View full text |Cite|
|
Sign up to set email alerts
|

Uncovering SARS-COV-2 vaccine uptake and COVID-19 impacts among First Nations, Inuit and Métis Peoples living in Toronto and London, Ontario

Abstract: Multigenerational colonial policies that aimed to assimilate First Nations, Inuit and Métis Peoples and appropriate land and resources have led to inequities across most major health outcomes for First Nations, Inuit and Métis living in urban, rural and remote geographies compared with non-Indigenous people in Canada, as well as striking gaps in access to equitable and culturally safe health care. 1,2 More than half of Indigenous Peoples in Canada live in urban areas. 3 In cities, jurisdictional complexities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…86,87 However, vaccination of FNIM living in urban and related homelands lagged. 88 Indigenous community leaders, health and social service providers, and PCCs (including Indigenous midwives, nurses, and physicians) brought attention to the importance of equitable geographic distribution and access to vaccines and rapidly implemented Indigenous-led vaccine initiatives to increase outreach and accessibility. did not have expertise in working with Black communities (e.g., the OMA module on addressing vaccine distrust among Black people).…”
Section: Community Outreach and Enhancing Equitymentioning
confidence: 99%
“…86,87 However, vaccination of FNIM living in urban and related homelands lagged. 88 Indigenous community leaders, health and social service providers, and PCCs (including Indigenous midwives, nurses, and physicians) brought attention to the importance of equitable geographic distribution and access to vaccines and rapidly implemented Indigenous-led vaccine initiatives to increase outreach and accessibility. did not have expertise in working with Black communities (e.g., the OMA module on addressing vaccine distrust among Black people).…”
Section: Community Outreach and Enhancing Equitymentioning
confidence: 99%
“…In Toronto, the mobile testing clinic run by Anishnawbe Health Toronto and the Auduzhe Mino Nesewinong comprehensive COVID-19 response clinic and outreach program were successful in mitigating barriers to accessing care using a "by community, for community" approach. 45 As another example, FNIM midwives played a leading role in responding to the unmet health and public health needs of the 88,000 FNIM people living in the city of Later in the pandemic, data limitations also meant that only a subset of primary care practices and clinicians could receive reports identifying their unvaccinated patients. 48 The experience of the COVID-19 vaccine rollout showed that when timely data were made available, many primary care teams, community organizations, and PHUs were able to band together with other system players in a data-driven, equity-focused response, as was the case in high-priority communities.…”
Section: Based Models Provides Superior Support For Covid-19 and Non-...mentioning
confidence: 99%
“…Ontario COVID-19 Science Advisory Table Brief on Primary Care Part 3: Lessons Learned for Strengthened Primary Care in the Next Phase of the COVID-19 Pandemicincluding creating a toolkit to provide guidance on engagement strategies for vaccine implementation for FNIM people in Ontario. These Indigenous-specific services are hypothesized to have contributed to the higher rate of COVID-19 testing among FNIM individuals compared to general Toronto populations prior to changes introduced to COVID-19 testing during the Omicron wave 45. Whether through OHTs or innovative approaches in high-priority communities that cross geographic boundaries, ongoing commitment to such partnered approaches that include PCCs as an essential element will be necessary.…”
mentioning
confidence: 99%
“…CMAJ has been made aware of errors that occurred in an article published Aug. 2, 2022. 1 The legends for panels B and D of Figure 1 read "OHC Toronto," "Toronto" and "Ontario" and should have read "OHC London," "London" and "Ontario. "…”
Section: Correction To "Uncovering Sars-cov-2 Vaccine Uptake and Covi...mentioning
confidence: 99%